(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Digitization is a process of increasing the reach and capacity of the financial service providers. It enhances the process of financial inclusion. The Government of Indian and other institutes are making tremendous efforts to increase the reach of financial services, still among the rural population it is very low. The innovations in digital modes of transactions has increased the capacity of the financial service providers manifolds. Hence, the present study was conducted to analyze the impact of digitization in rural parts of Assam. The business correspondents of four banks, their customers, and parameters of digital infrastructure in the location was studied. It was observed that in the selected location financial and digital literacy among the borrowers is low. The reasons cited by the customers for not using digital modes of transactions are related to their low level of awareness about the product and lack of confidence.